A ten-year-old child's representations of motion. - Kendall, Amber. (Tufts Archival Research Center, 2005)
This paper presents the case study of a 10-year-old boy and the various representations he produces to express his ideas about the motion of a car through three clinical interviews. This work also provides an initial exploration of using animation (SAM Animation software, http://www.samanimation.com) as an alternative to conventional graphing in the elementary classroom, to quantitatively represent understandings of motion in a form closer to children's spontaneous figurative drawing. The goals of this study were to explore the invented representations of motion produced by a 10 year old boy; how his paper and pencil representations compared to those produced through animations; and how his understandings of time, displacement, speed, and acceleration were expressed through the representations he created. Two types of drawings (figurative and non-figurative) and one animation of the motion of a car produced by an elementary student were examined to compare the resources used in their creation and the ways in which they allowed me to explore the students_ï¿½_ understandings of motion. Many resources previously observed in other students_ï¿½_ works, such as drawings, words, _ï¿½ï¿½more is more,_ï¿½ï¿½ temporal sequences, and line segments were present in all three types of representation. The figurative drawings exhibited rudimentary understandings of motion, representing changes in the car_ï¿½_s speed as snapshots rather than continuous accelerations. The non-figurative representations depicted slightly more quantitative information about speed and acceleration using almost the same set of resources, but incorporating the idea of acceleration as changing speed. The child recognized the potential for demonstrating _ï¿½ï¿½real life_ï¿½ï¿½ motion within the medium of animation, but his actual product shared more similarities with the resources of the static figurative drawings that he had produced than his non-figurative representations, in which he represented quantities more explicitly. However, the animation_ï¿½_s explicit treatment of time, and small ___t, provided the basis for the exploration of the _ï¿½ï¿½A x B = C_ï¿½ï¿½ relationships between speed, displacement, and duration, and speed, acceleration and duration. The three forms of representation provided for varied contexts through which his understandings of speed, time, and acceleration articulated in the drawings could be explored in the resulting discussions about his productions.